Impact of Play on Early Childhood - Mehraj, Radiya (My University, 2024)
In this essay, the concept of play is explored within the context of early childhood education, emphasizing its definition, functions, and developmental significance. This study examines many theoretical viewpoints and their consequences as it explores the multidimensional character of play, drawing on the insights of scholars and researchers. It also looks at specific types of play, such as play in the outdoors, play for children with special needs, and play's relationship to education. This investigation emphasizes the critical role that play plays in early childhood and development, emphasizing the value of play in promoting learning experiences and holistic growth.
Keywords: play, development, early childhood education, history, learning, children with special needs